2. PENGARUH FENOMENA RESOURCE CURSE TERHADAP PRAKTEK PENCURIAN DAN TRANSSHIPMENT MINYAK DI NIGERIA PADA PERIODE 2010-2014 - Wahyu Setiawan; Fendy Eko Wahyudi; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Around 250.000 barrels of oil stolen every day in Nigeria during 2013, and estimatedaround 3-8 billion USD loss every year. To stop this illegal activity, Nigeria governmentunder President Jonathan has made several measurements. These measurements remainunable to stop or limiting this illegal activity. Analyzing the interaction inside the oil-theftnetwork, and the movement of the stolen oil on value added chain, one of the main factorsthat drive this activity is the rent-seeking behavior. Rent-seeking behavior raises andparalyzing on many countries with resource curse environment. Elimination of drivingfactors such as rent seeking, high political cost, and international demand is very importantto curb this activity into a complex, looted, and hard-to-eliminate crime.